Treatment with Bixin-Loaded Polymeric Nanoparticles Prevents Cigarette Smoke-Induced Acute Lung Inflammation and Oxidative Stress in Mice - Alexsandro Tavares Figueiredo-Junior; Samuel Santos Valença; Priscilla Vanessa Finotelli; Francisca de Fátima dos Anjos; Lycia de Brito-Gitirana; Christina Maeda Takiya; Manuella Lanzetti (MDPI AG, 2022)
The use of annatto pigments has been evaluated as a therapeutic strategy in animal models of several health disorders. Beneficial effects were generally attributed to the inhibition of oxidative stress. Bixin is the main pigment present in annatto seeds and has emerged as an important scavenger of reactive oxygen (ROS) and nitrogen species (RNS). However, this carotenoid is highly hydrophobic, affecting its therapeutic applicability. Therefore, bixin represents an attractive target for nanotechnology to improve its pharmacokinetic parameters. In this study, we prepared bixin nanoparticles (npBX) and evaluated if they could prevent pulmonary inflammation and oxidative stress induced by cigarette smoke (CS). C57BL/6 mice were exposed to CS and treated daily (by gavage) with different concentrations of npBX (6, 12 and 18%) or blank nanoparticles (npBL, 18%). The negative control group was sham smoked and received 18% npBL. On day 6, the animals were euthanized, and bronchoalveolar lavage fluid (BALF), as well as lungs, were collected for analysis. CS exposure led to an increase in ROS and nitrite production, which was absent in animals treated with npBX. In addition, npBX treatment significantly reduced leukocyte numbers and TNF-α levels in the BALF of CS-exposed mice, and it strongly inhibited CS-induced increases in MDA and PNK in lung homogenates. Interestingly, npBX protective effects against oxidative stress seemed not to act via Nrf2 activation in the CS + npBX 18% group. In conclusion, npBX prevented oxidative stress and acute lung inflammation in a murine model of CS-induced acute lung inflammation.